SPECIAL EDUCATION: WORKING WITH STUDENTS AND STUDENTS DIAGNOSED WITH LEARNING DISORDERS ASSOCIATED WITH LANGUAGE AND COMMUNICATION - Juliane Barros Generoso, Cibele; Cristiane Barros Moreira, Érica (Revista Gênero e Interdisciplinaridade, 2023)
The acquisition of language is part of the historical development of human beings, it is one of the characteristics that differentiates them from other animals. Through language, subjects establish social relationships, express themselves, learn and teach, understand signs and incorporate social standards. However, there are many students who have educational needs related to learning disorders associated with language and communication. This article has the general objective of reflecting on this theme. As specific objectives, it is intended to reflect on the difference between learning problems and difficulties, and to discuss learning disorders and language acquisition. The text was prepared through a literature review, based on articles, books, periodicals, among other materials. It is concluded that the specialized educational service does not have students with learning disorders associated with language and communication as a target audience, however, education professionals, committed to inclusion, must observe and analyze the difficulties that these subjects face and seek ways to to implement a public, free, secular and quality education.